The nexus between attribution theory and racial attitudes: a test of racial attribution and public opinion of capital punishment. Issue 4 (2nd October 2018) - Trahan, Adam; Laird, Kaleigh
ABSTRACT: Research has shown that attribution theory and racial attitudes are among the most consistent attitudinal predictors of capital punishment opinion. This study explores the overlap of these two constructs, racial attribution, and its ability to account for support and opposition to the death penalty. Using data from the 1972–2016 cumulative data file of the General Social Survey, three logistic regression models were used to analyze the effect of internal and external racial attribution on capital punishment opinions for (a) the aggregate sample, (b) White respondents only, and (c) Black respondents only. Respondents were asked whether racial inequalities were due to structural disadvantages or personal deficiencies of Black Americans. Findings showed that respondents in all three models were more likely to support the death penalty when they attributed racial inequalities to personal deficiencies of Blacks and less likely to support the death penalty when they endorsed structural disadvantages, although the effects were somewhat muted for Black respondents. These findings suggest that ongoing public support for capital punishment in the United States is based at least in part on a fundamental attribution error in which Whites and some Blacks alike blame Blacks for their own deprivation.